Love's long journey [videorecording (DVD)] - Cottrell, Erin; Savage, John, 1949-; Bartholomew, Logan; Midkiff, Dale, 1959-; Bedard, Irene, 1967-; Oke, Janette, 1935- (Love comes softly, 2006)
Missie and Wille LaHaye are on their way to the west. The couple become rugged pioneers as they face all kinds of hardships, including death. Missie fights homesickness, boredom, and being pushed to the limit. Can her faith help her through?